Outdoor science lab for kids : 52 family-friendly experiments for the yard, garden, playground, and park - Heinecke,Liz Lee (Quarry Books, an imprint of Quarto Publishing Group USA Inc., 2016)
At-home science provides an environment of freedom, creativity and invention that is not always possible in a school setting. It's simple, inexpensive, and fun to whip up a number of amazing science experiments in your own backyard. Science can be found all around in nature. Outdoor Science Lab for Kids offers 52 fun STEM activities for families to do together. The experiments can be used as individual projects, for parties, or as educational activities for groups. Outdoor Science Lab for Kids will tempt families to learn about physics, chemistry, biology, and nature, plus, they'll learn scientific survival skills and even take some experiments to the playground! Many of the experiments are safe enough for toddlers and exciting enough for older kids, so families can discover the joy of science and STEM education together.